Manajemen Laba Perbankan (Studi Pada Bank Terdaftar di Bursa Efek Indonesia Periode 2010-2012) - Taufiq Hidayat; Oriza Amouri (Jurnal Keuangan dan Perbankan, 2015)
The objective of this research was to examine the influence of several corporate governance mechanisms, such as board of independent commissioners composition and size of audit committee, firm size, and information asymmetric on the indication of earnings management practice in public bank companies listed in Indonesia Stock Exchange. The sample of this research is all of public bank companies existed in Indonesia in the year 2010-2012. This research used purposive sampling to determine sample. Total sample for this research is 25 public bank companies. This research used multiple regression. The result shows that board of independent commissioners had a negative effect to earning management; size of audit committee had not significant to earning management; firm size had not significant to earning management; information asymmetric had a negative effect to earning management